Adsorption of Acid Blue 161 (AB 161) Dye from Water by Multi-Walled Carbon Nanotubes - Geyikçi, F. (Taylor & Francis Inc, 2013)
The adsorption properties of acid blue 161 (AB 161) from aqueous solution onto multi-walled carbon nanotubes (MWCNTs) was studied as a function of time, pH and initial AB 161 concentration. The maximum adsorption yield (91.68%) was obtained at the conditions of pH 3.0, MWCNTs dosage of 0.1 g/L, contact time of 60 minutes, for initial AB 161 concentration of 50 mg/L and temperature of 25°C. Also, Langmuir, Freundlich and Temkin isotherms and three kinetic models were applied to fit the experimental data. Both Freundlich and Temkin models agree well with experimental data. The adsorption capacity of MWCNT was compared with activated carbon (AC). The results suggest that MWCNTs have good potential application in dye adsorption. © 2013 Taylor & Francis Group, LLC.
Keywords: Acid Blue 161; Adsorption; Multi-Walled Carbon Nanotubes